2020
DOI: 10.1111/jar.12752
|View full text |Cite
|
Sign up to set email alerts
|

The impact of self‐advocacy organizations on the subjective well‐being of people with intellectual disabilities: A systematic review of the literature

Abstract: This is the first systematic review to focus explicitly on the impact of self-advocacy on the subjective well-being of people with intellectual disabilities. It builds upon another recently published systematic literature review that explored the psychological and social impact of self-advocacy on its members (Fenn & Scior, 2019). While some of the outcomes reported in this study overlap with the previous review, this article further contributes to knowledge regarding the impact of self-advocacy by identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
(193 reference statements)
2
24
0
Order By: Relevance
“…Importantly, thanks to participation in the project, people with disability can feel understood and act as a role model. Similar results have been obtained in other studies on self-advocacy (Beart et al, 2004;Booth & Booth, 1999;Clarke et al, 2015;Stalker, 1997) and were revealed in systematic reviews of the studies on psychological and social benefits of group self-advocacy to people with ID (Fenn & Scior, 2019;Tilley et al, 2020). One of the respondents also mentioned that self-advocacy supported him in resilience and finding a way to solve his problems and to find his way as a person with a disability.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Importantly, thanks to participation in the project, people with disability can feel understood and act as a role model. Similar results have been obtained in other studies on self-advocacy (Beart et al, 2004;Booth & Booth, 1999;Clarke et al, 2015;Stalker, 1997) and were revealed in systematic reviews of the studies on psychological and social benefits of group self-advocacy to people with ID (Fenn & Scior, 2019;Tilley et al, 2020). One of the respondents also mentioned that self-advocacy supported him in resilience and finding a way to solve his problems and to find his way as a person with a disability.…”
Section: Discussionsupporting
confidence: 86%
“…A person might also build a positive identity, develop a sense of self and strengthen self-determination, sense of empowerment, and resilience (Clarke et al, 2015). Data from interviews with self-advocates with ID suggest that the abovementioned benefits might be gained from such activity (Anderson & Bigby, 2017;Caldwell, 2011;Gilmartin & Slevin, 2010;Hall, 2005;McNally, 2003; for the recent systematic reviews see also : Fenn & Scior, 2019;Tilley et al, 2020). Given the relative independence of the Anderson & Bigby's model from cultural contexts and the fact that the theory is grounded in the real experiences of people with ID from various self-advocacy groups, this model might serve as an important reference point when discussing experiences of self-advocates worldwide.…”
mentioning
confidence: 99%
“…Although there are several studies that focus on a particular aspect of SWB in physical and mental health (Zautra and Hempel, 1984 ; Vothknecht et al, 2011 ; Ngamaba et al, 2017 ; Mansfield et al, 2018 ; Vescovelli et al, 2018 ; Buecker et al, 2020 ; Moura and Hamdan, 2020 ; Tilley et al, 2020 ; Todd et al, 2021 ), studies on pregnancy and pregnant women have received little attention. Several reviews have looked at the quality of life (QoL) of pregnant women (Mogos et al, 2013 ; Lagadec et al, 2018 ), yet none have specifically focused on the association between pregnant women and SWB.…”
Section: Introductionmentioning
confidence: 99%
“…Prosocial behavior positively correlates with gratitude, 76 which in turn exerts a positive influence on subjective well-being. 77 Subjective well-being positively correlates with prosocial behavior, 78 and an online study suggested that altruistic behavior positively correlates with subjective well-being. 79 Additionally, positive feelings are a significant outcome variable of prosocial behavior.…”
Section: Introductionmentioning
confidence: 99%